Identifying and Promoting Transition Evidence-Based Practices and Predictors of Success: A Position Paper of the Division on Career Development and Transition - Mazzotti, Valerie L.; Rowe, Dawn A.; Cameto, Renee; Test, David W.; Morningstar, Mary E. (Career development and transition for exceptional individuals, 2013)
This position paper describes the Division of Career Development and Transition’s stance and recommendations for identifying and promoting secondary transition evidence-based practices and predictors of postschool success for students with disabilities. Recommendations for experimental research, correlational research, and secondary analysis of the National Longitudinal Transition Study–2 data are provided. Finally, suggestions related to planning for future research in the area of secondary transition are discussed.